Sexual activity and romantic relationships after burn injury: A Life Impact Burn Recovery Evaluation (LIBRE) study. Issue 7 (November 2020) - Ohrtman, Emily A.; Shapiro, Gabriel D.; Wolfe, Audrey E.; Trinh, Nhi-Ha T.; Ni, Pengsheng; Acton, Amy; Slavin, Mary D.; Ryan, Colleen M.; Kazis, Lewis E.; Schneider, Jeffrey C.
Highlights: No differences in romantic relationship status were found between adult burn survivors and the general U.S. population. Adult burn survivors were more likely to report being sexually active than a sample of the general U.S. population. Adults with hand burns were more likely to report being sexually active and in a romantic relationship. Abstract: Background: Engaging in healthy sexual activity and romantic relationships are important but often neglected areas of post-burn rehabilitation. The degree to which persons with burn injuries engage in sexual activity and romantic relationships is not well understood. This study examined demographic and clinical characteristics predicting engagement in sexual activity and romantic relationships in a sample of adult burn survivors compared to a general United States sample. Methods: Data for the adult burn survivor sample were from 601 adult burn survivors who participated in field-testing for the calibration of the Life Impact Burn Recovery Evaluation (LIBRE) Profile, a burn-specific instrument assessing social participation on six scales including sexual activity and romantic relationships. Comparison data were obtained from a general population sample of 2000 adults through sample matching. Demographic predictors of sexual activity and romantic relationship status were examined in each sample using modified Poisson regression analyses. Clinical predictors of engaging in sexual activity and romantic relationships were also examined in the LIBRE sample. Results: Participants were slightly more likely to report being sexually active in the adult burn survivor sample than in the general sample (65% vs. 57%, p < 0.01). There was not a significant difference in romantic relationship status between the two samples (64% vs. 62%, p = 0.31). In multivariable regression analyses, men in both samples were more likely to report being in a sexual relationship (RR in LIBRE sample = 1.23, 95% CI 1.08–1.39; RR in general sample = 1.10, 95% CI 1.02–1.18). Participants in both samples who were not working were less likely to report being sexually active or in a romantic relationship (RRs ranging from 0.73 to 0.83, p < 0.05 for all estimates). In the adult burn survivor sample, respondents with hand burns were more likely to report being sexually active and in a romantic relationship (RR = 1.16, 95% CI 1.01–1.33). Time since burn injury, burn size, and burns to other critical areas were not significantly associated with either outcome in adjusted analyses. Conclusions: The likelihood of engaging in sexual activity and romantic relationships is similar among adult burn survivors and the comparison group representing a general United States sample of adults. Further research addressing sexual activity and romantic relationships after burn injuries will help to foster better patient-clinician dialogue, pinpoint barriers, design interventions, and allocate appropriate resources.